Neutrophil TLR4 expression is reduced in the airways of infants with severe bronchiolitis. Issue 9 (3rd June 2009) - Halfhide, C P; Brearey, S P; Flanagan, B F; Hunt, J A; Howarth, D; Cummerson, J; Edwards, S; Hart, C A; Smyth, R L
Abstract : Background: In respiratory syncytial virus (RSV) bronchiolitis, neutrophils account for >80% of cells recovered from the airways in bronchoalveolar lavage (BAL) fluid. This study investigated neutrophil activation and Toll-like receptor (TLR) expression in the blood and lungs of infants with severe RSV bronchiolitis. Methods: BAL fluid and (blood) samples were collected from 24 (16) preterm and 23 (15) term infants ventilated with RSV bronchiolitis, and 12 (8) control infants. Protein levels and mRNA expression of CD11b, myeloperoxidase (MPO) and TLRs 2, 4, 7, 8 and 9 were measured in neutrophils. Results: Blood neutrophils had more CD11b in preterm and term infants with RSV bronchiolitis than control infants (p<0.025) but similar amounts of MPO. BAL fluid neutrophils from infants with RSV bronchiolitis had greater amounts of CD11b and MPO than blood neutrophils and BAL fluid neutrophils from controls (p<0.01). Blood neutrophils from term infants with RSV bronchiolitis had less total TLR4 protein than preterm infants with RSV bronchiolitis (p = 0.005), and both had less than controls (p<0.04). Total TLR4 for each group was greater in BAL fluid neutrophils than in blood neutrophils. Blood neutrophils from preterm infants with RSV bronchiolitis had greater TLR4 mRNA expression than term infants with RSV bronchiolitis (p = 0.005) who had similar expression to controls (p = 0.625). Conclusions: In infants with severe RSV bronchiolitis, neutrophil activation starts in the blood and progresses as they are recruited into the airways. Total neutrophil TLR4 remains low in both compartments. TLR4 mRNA expression is unimpaired. This suggests that neutrophil TLR4 expression is deficient in these infants, which may explain why they develop severe RSV bronchiolitis.